2017
DOI: 10.1016/j.biocontrol.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Fungal community in olive fruits of cultivars with different susceptibilities to anthracnose and selection of isolates to be used as biocontrol agents

Abstract: A B S T R A C TOlive anthracnose is an important fruit disease in olive crop worldwide. Because of the importance of microbial phyllosphere to plant health, this work evaluated the effect of cultivar on endophytic and epiphytic fungal communities by studying their diversity in olives of two cultivars with different susceptibilities to anthracnose. The biocontrol potency of native isolates against Colletotrichum acutatum, the main causal agent of this disease, was further evaluated using the dual-culture method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
6
31
0
2
Order By: Relevance
“…The endophytic fungal communities earlier found in aboveground olive tree compartments (phyllosphere and carposphere) by high-throughput sequencing 23 or a culture-dependent approach 20 , differed from belowground communities reported in our study. This outcome reinforces previous reports showing important differences between above- and belowground olive fungal communities, regardless the methodological approach implemented to study them 20,22,23 . Interestingly enough, Sordariomycetes was also the most abundant class found in olive fruits regardless or not the presence of anthracnose symptoms 23 , pointing to the fact that this fungal class seems to be ubiquitously colonizing the interior of olive tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The endophytic fungal communities earlier found in aboveground olive tree compartments (phyllosphere and carposphere) by high-throughput sequencing 23 or a culture-dependent approach 20 , differed from belowground communities reported in our study. This outcome reinforces previous reports showing important differences between above- and belowground olive fungal communities, regardless the methodological approach implemented to study them 20,22,23 . Interestingly enough, Sordariomycetes was also the most abundant class found in olive fruits regardless or not the presence of anthracnose symptoms 23 , pointing to the fact that this fungal class seems to be ubiquitously colonizing the interior of olive tissues.…”
Section: Discussionsupporting
confidence: 90%
“…Cobrançosa 20 were screened by a culture-dependent method to compare the fungal communities between above- and belowground compartments. Microbial communities of the olive phyllosphere and carposphere have been analyzed using denaturing gradient gel electrophoresis (DGGE) 21 , isolation of fungi in culturing media 22 and high-throughput sequencing of both fungal 23 and prokaryotic 24 communities.…”
Section: Introductionmentioning
confidence: 99%
“…While studies on specific beneficial components of the olive-associated microbiota have been conducted, some of them aiming to isolate and characterize biological control agents (BCA) against VWO [12][13][14], only very few examples are available on whole indigenous olive microbial communities [15,16] and their potential relationship with susceptibility to biotic constraints [17]. Recently, we described the belowground microbial communities of a range of olive cultivars from different geographical origin grown under the same climatic, agronomical and soil conditions, and in the absence of V. dahliae pressure [18].…”
Section: Introductionmentioning
confidence: 99%
“…A scanning electron microscope showed that the Trichoderma endophytes cause deformities in the mycelia of Pythium aphanidermatum and Rhizoctonia solani, such as hyphal fragmentation, perforation, lysis, and mycelial degeneration [28]. A strain of Trichoderma harzianum showed in vitro growth contact points that suggest mycoparasitic activity against Fusarium solani [34]. Endophytic and epiphytic fungi isolated from fruits of organic Olea europaea were able to inhibit mycelial growth, germination, and sporulation and cause pathogenic hyphae abnormalities of Colletotrichum acutatum, particularly at mycelial contact [35].…”
Section: Biological Controlmentioning
confidence: 99%